Aplicação da metodologia do Rio Rural no âmbito do Comitê de Bacias do Piabanha - Cesar, Pedro Igor Austregésilo Corrêa (2020)
This dissertation, based on the methodology of Rio Rural program conducted by the State Secretariat of Agriculture, Fisheries and Supply of the State of Rio de Janeiro, funded by the World Bank, aims to identify possible adaptations for application in the Piabanha River Basin Committee, aiming at the rational water use. In this hydrographic region, the Bonfim community has been chosen as study area because it is one of the catchments in which there is a conflict of water use between agriculture and water supply which stood out by its community organization during the development of Rio Rural Program. In 2016, EMATER applied the Participatory Rural Diagnosis questionnaires, which subsequently gave rise to the Microbasin Executive Plan in the community, with a 2-year long plan to solve the prioritized problems. In order to assess its current status, after the established deadline, the questionnaires have been applied once more, through interviews with local stakeholders, determining which goals had been achieved and identifying possible causes of those which had not been met, in addition to opportunities of actions of the Piabanha Watershed Committee aimed at improving water availability and water quality in order to allow multiple uses of water thus increasing water availability and improving water quality.